2019
DOI: 10.1002/jwmg.21749
|View full text |Cite
|
Sign up to set email alerts
|

Greater sage‐grouse habitat function relative to 230‐kV transmission lines

Abstract: Greater sage‐grouse (Centrocercus urophasianus) is a landscape‐level species that requires large tracts of intact sagebrush (Artemisia spp.). Loss of functional habitat resulting from increased demand for energy generation, transmission, and distribution within greater sage‐grouse habitats in the western United States has the potential to negatively affect this species. We monitored 346 radio‐marked female greater sage‐grouse from 2009 to 2014 to evaluate the potential effects of 27‐m‐tall, 230‐kilovolt (kV) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…We assessed six different distance thresholds (i.e., candidate impact zones) to identify the impact zone that garnered greatest support from the data. Three candidate distances were based on studies relating energy development to sage-grouse populations, including ∼2 km [ 29 , 30 ], 5 km [ 31 , 32 ], and 10 km [33] . We included three additional candidate impact zones (15, 20, and 30 km) to evaluate sequentially larger areas and avoid possible truncation of a distance effect.…”
Section: Example Using Real Datamentioning
confidence: 99%
“…We assessed six different distance thresholds (i.e., candidate impact zones) to identify the impact zone that garnered greatest support from the data. Three candidate distances were based on studies relating energy development to sage-grouse populations, including ∼2 km [ 29 , 30 ], 5 km [ 31 , 32 ], and 10 km [33] . We included three additional candidate impact zones (15, 20, and 30 km) to evaluate sequentially larger areas and avoid possible truncation of a distance effect.…”
Section: Example Using Real Datamentioning
confidence: 99%
“…We chose the HSI model because it is simple to run and does not need the presence data and absence data of the research species (Hua et al, 2012;Frantz et al, 2018;Lebeau et al, 2019). Compared with maximum entropy (MaxEnt), general additive model (GAM), general liner model (GLM), boost regression tree (BRT) and other models that need these data (Zurell et al, 2012;Brambilla et al, 2020), HSI has no training process, so it needs to determine the weight in advance, and this weight directly affects the accuracy of the model, so we carefully determine the weight, combined with the analytic hierarchy process and entropy weight method.…”
Section: The Framework For Habitat Suitability Assessmentmentioning
confidence: 99%
“…Survival of adult female greater prairie-chicken (Winder et al 2014b Several studies reported a positive effect of wind-energy facilities on adult female survival: Winder et al (2014b) found that annual survival of greater prairie-chickens was substantially greater during the 3-year postconstruction period than the 2-year pre-construction period (57% v. 32%), and LeBeau et al (2017aLeBeau et al ( , 2019 found survival of greater sage-grouse and lesser prairie-chicken was greater in areas that contained a higher density of wind-energy infrastructure (roads and turbine pads). Explanations for higher post-development survival are speculative but generally involve potential negative effects of development on common predators of prairie grouse (i.e., a positive indirect effect on grouse; Winder et al 2014b, LeBeau et al 2017a.…”
Section: Adult Survivalmentioning
confidence: 99%
“…Changes in patterns of habitat selection that are indicative of avoidance may arise more quickly and be more readily detectable but must translate into demographic changes if they are to produce population‐level consequences and thus prove relevant for conservation. Coupled patterns of avoidance, isolation, diminished vital rates, and ultimately population decline are apparent from studies of prairie grouse responses to other forms of energy development, such as transmission lines (Aldridge and Boyce 2007, Holloran et al 2010, Gibson et al 2018, LeBeau et al 2019).…”
Section: Effects Of Wind Energy On Prairie Grousementioning
confidence: 99%
See 1 more Smart Citation